Lens complementation system for the genetic analysis of growth, differentiation, and apoptosis in vivo. - Liégeois, N J (1996)
A genetic approach has been established that combines the advantages of blastocyst complementation with the experimental attributes of the developing lens for the functional analysis of genes governing cellular proliferation, terminal differentiation, and apoptosis. This lens complementation system (LCS) makes use of a mutant mouse strain, aphakia (ak), homozygotes of which fail to develop an ocular lens. We demonstrate that microinjection of wild-type embryonic stem (ES) cells into ak/ak blastocysts produces chimeras with normal ES-cell-derived lenses and that microinjection of Rb-/- ES cells generates an aberrant lens phenotype identical to that obtained through conventional gene targeting methodology. Our determination that a cell autonomous defect underlies the aphakia condition assures that lenses generated through LCS are necessarily ES-cell-derived. LCS provides for the rapid phenotypic analysis of loss-of-function mutations, circumvents the need for germ-line transmission of null alleles, and, most significantly, facilitates the study of essential genes whose inactivation is associated with early lethal phenotypes.